The acceptance level on GST implementation in Malaysia / Nur Syazwani Mohammad Fadzillah and Zuhariah Husin - Mohammad Fadzillah, Nur Syazwani; Husin, Zuhariah (Universiti Teknologi MARA Cawangan Pahang, 2016)
Generally, tax is recognized as one of the main sources of government’s revenue and Goods and Services Tax (GST) is an example of tax that contributes to it. This tax has been implemented in many countries such as Canada, Australia, and New Zealand. Roughly, 90 percent of the world’s population lives in countries with GST. In Malaysia, GST has been implemented on 1 April 2015 at 6% rate and it replaced the present consumption tax comprising the sales tax and the service tax. The issue on GST has been raised by the Malaysian Government as an approach to reduce its deficit. GST is imposed on goods and services throughout production-distribution stages in the supply chain including importation of goods and services. The tax is embedded in the price of goods and services transacted. However, the implementation of GST in Malaysia has called many arguments from various parties including academics, professionals and the taxpayers on how GST affects goods prices, either increase or decrease. The consumers are worried of the significant price increases on basic needs. With the relatively high living costs, significant price increases due to GST is considered as another burden for the taxpayers. Therefore, the main objective of this study is to investigate the level of acceptance of taxpayers regarding GST implementation. This study utilised survey questionnaires distributed to UiTM Pahang’s lecturers. The findings hopefully will shed a clearer view on the taxpayers’ acceptance level of GST to the tax authorities.